Long-Term Outcomes With Drug-Eluting Balloon for the Treatment of In-Stent Restenosis and De Novo Lesions: The Novara-Biella-Trento (NOBITRE) Registry. (May 2023) - Verdoia, Monica; Zilio, Filippo; Viola, Orazio; Brancati, Marta Francesca; Fanti, Diego; Soldà, Pier Luigi; Rognoni, Andrea; Bonmassari, Roberto; De Luca, Giuseppe
Drug-coated balloons (DCBs) have emerged for percutaneous coronary interventions (PCI) of in-stent restenosis or particular anatomical subsets. We provide a real-world analysis of the prognostic determinants and long-term outcomes of patients treated with DCB for any lesion in a comprehensive multicenter registry. The primary study endpoint was the occurrence of major cardiovascular events (MACE: composite of all-cause death, myocardial infarction, and target vessel revascularization) at the longest available follow-up. We included 267 patients (196 treated for in-stent restenosis and 71 for de novo lesions), with a median follow-up of 616 [368–1025] days. MACE occurred in 70 (26.2%) of the patients and related with higher rates of in-stent restenosis (P = .04), longer and more type C lesions ( P = .05 and P = .04). At multivariate Cox-regression, type C lesions emerged as the only independent predictor of MACE (adjusted OR [95% CI] = 1.83[1.13–2.97], P = .014), mainly driven by target vessel revascularization (adjusted OR[95% CI] = 1.78[1.05–2.95], P = .03) not conditioning survival. In-stent restenosis emerged as major determinant of TLF (adjusted OR[95% CI] = 2.59[1.17–5.75], P = .02). DCBs represent a treatment option for any lesion; however, type C and restenotic lesions are associated with an increased risk of MACE and target lesion failure, where the optimal strategies for patients' selection and lesion preparation are still undefined.